Magnetoresistance of Monolayer Graphene With Short‐Range Disorder. Issue 6 (28th February 2019) - Vasileva, Galina; Alekseev, Pavel; Vasilyev, Yuri; Dmitriev, Alexander; Kachorovskii, Valentin; Smirnov, Dmitri; Schmidt, Hennrik; Haug, Rolf
Abstract : The effect of magnetic field on electron transport in graphene monolayers with various levels of impurity doping is studied. In samples with low impurity doping a square root magnetoresistance appears away from the Dirac point and no such magnetoresistance is observed in low mobility monolayers with high impurity doping. The difference in magnetoresistance is attributed to different types of scattering mechanisms in various samples. Our data for graphene monolayers with low impurity concentration shows a good agreement with theory over a wide range of magnetic fields. Abstract : The effect of short‐range scattering on the magnetotransport in monolayer graphene is discussed both theoretically and experimentally. It is shown that in a wide interval of magnetic field the magnetoresistance obeys a square root law. A simple physical picture of the discussed phenomenon is developed.